A Cross-Sectional Study on Gastrointestinal Parasites in Backyard Poultry in Krishna District, Andhra Pradesh, India - B. Anupama; Malakondaiah, P.; Sreedevi, C.; Kumar, P. Ravi; Satheesh, K. (International Journal of Livestock Research, 2020)
A total of 1447 desi birds’ samples (faeces, gastrointestinal tracts) collected from various villages in Krishna district, Andhra Pradesh were examined from July 2015 to June 2016 to determine the prevalence of gastrointestinal (GI) parasites. The overall prevalence was 74.22 per cent. Mixed infection was more frequent (70.39 %) and cestodes were the common parasites in all infected birds. No trematode parasite was identified. The species identified includes Amoebotaenia sphenoides, Cotugnia digonopora, Davainea proglottina, Hymenolepis carioca, Raillietina cesticillus, R. echinobothridia and R. tetragona in cestodes, Ascaridia galli, Capillaria spp., Heterakis gallinarum, Strongyloides avium, Subulura brumpti, Tetrameres mohtedai and Dispharynx spiralis in nematodes and Eimeria spp. in protozoa. The prevalence of infection was increased with advance in age. Statistically there was no significant relationship between the prevalence of infection and age, sex and seasons (P>0.05). Cotugnia digonopora was the highest prevalent parasite. Dispharynx spiralis was exclusively found in chicks and in summer. Tetrameres mohtedai was exclusively identified in female bird.